Power and position-oriented process monitoring of freeform abrasive machining - Brazel, Emma (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2013)
Abrasive machining is used for the generation of freeform femoral implant surfaces in the biomedical industry. The abrasive machining operation is typified by high speed material removal in multiple axes, difficult-to-machine material and the use of hard abrasives on toroidal shaped grinding wheels. Such machining operations are often inefficient due to conservative choices of machining parameters, which are based upon trial-and-error approaches in order to maintain workpiece surface integrity. Process monitoring is necessary to achieve process optimisation, through the identification and avoidance of process disturbances, which could cause poor surface integrity at chosen machining parameters.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin